Implementation and Relevance of Curriculum of Health Insurance Diploma at the Health Insurance Education Institutions - Gunarto, Catur Septiawan; Hakim, Achmad Lukman (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Good quality curriculum is very important to create highly competitive graduates, thereby it require curriculum review regularly to adjust recent health insurance institutions needs based on graduates users needs particularly at the Diploma Program of Health Insurance STIKIM. The research aims to understand the implementation and relevance of the diploma program curriculum in health insurance at the health insurance education institutions. We used a qualitative method by interviewing 5 informants who consists of the Head of Health Insurance Diploma Program STIKIM, 1 lecturer, 1 alumni, 1 student, and 1 graduate user, and then the data were analyzed using Bogdan and Biklen model. The result showed curriculum implementation of Health Insurance Diploma Degree STIKIM 2010 academix year still relevant to the expected measure, this reflected from alumni is easier getting a job in their respective field. However, there are still weakness in the implementation of the curriculum such as internship program for final year student is still limited due to lack of cooperation with government and private sectors. This study concluded that curriculum of Health Insurance Diploma Program STIKIM 2010 academic year is still relevant to the to the needs of graduates users, so for now it is no needs to update the curriculum of Health Insurance Diploma Program STIKIM 2010 academic year.